PROSES PENGAMBILAN KEPUTUSAN KEPALA MADRASAH DALAM MENCAPAI VISI DAN MISI PENDIDIKAN ISLAM - Huda, Alamul; Sukarman, Sukarman; Lutfiyah, Lutfiyah; Wahyuni, Titik (LPPM UM Metro, 2024)
In the world of education, the principal certainly has the task of making decisions within a school. This study aims to determine the decision-making process of the madrasah principal in achieving the vision and mission of Islamic education at MI Sultan Fatah Demak. This study uses qualitative methods and data collection in the form of observation, interviews, and documentation. The results of this study indicate that the decision-making process is based on 5 stages, namely the problem-solving stage, determining criteria and identifying alternative problem-solving, the stage of assessing alternative problem-solving, the stage of selecting the best latent, and the stage of determining decisions that according to respondents are wise in making decisions. The madrasah principal pays attention from the stage of formulating problems and identifying problems to determining decisions or disseminating decisions taken. However, there are suggestions from respondents that a new method needs to be created so that when making decisions it is not influenced by any party.